Homotrema rubrum taphonomy as an indicator of sedimen transport of the Bangka Island Waters, North Minahasa. (July 2018) - Alam, M; Zuraida, R; Sari Yuliadi, L P; Lili, W; Nurruhwati, I
Abstract: The determination of current direction from sedimentary deposits were based on silisiclastic deposits that behave differently than biogenic fragment-rich deposit. The objectives of this research are to determine biogenic sediment transport pathway of Bangka Island water, North Minahasa, by the taphonomy of benthic foraminifer Homotrema rubrum and to verify the reconstructed pathway with sea surface currents data. This study used twelve surface sediment samples that were acquired by grab sampler in 2016 and 2014-2016 annual average sea surface current data from INDESO that was generated by OPA/NEMO model. The result of this study shows that samples with higher degree of taphonomy are located closer to coral reef which forms the source of H. rubrum while samples with lower degree of taphonomy are located further from the source. Sediment transport pathway reconstructed from H. rubrum taphonomy shows inflow of water from the north and west part of the islands and West Likupang Strait to the east and flowing out of East Likupang Strait. This direction corresponds to annual sea surface current derived from INDESO. This study also shows that H. rubrum taphonomy can be used as sediment transport indicator in areas that are dominated by biogenic sediments.